Desulfurization of Dibenzothiophene from Model Oil by Aluminum Ammonium Sulfate/Urea (Alum) Ionic Liquid Analogue - Emad Faseh, Noor; M. A. Abood, Hadi (Al-Nahrain Journal of Science, 2020)
Petroleum is the most important source of energy which is required to be free of sulfur. Ionic liquid analogue was used to desulfurize Model oil at several conditions including different concentration of dibenzothiophene (DBT), time of extraction, temperature and ionic liquid analogue to Model volume ratios. The cheap and easy made ionic liquid analogue is a mixture of 1:5 mole ratio of Aluminum ammonium sulfate.12H2O: Urea (Alum).The desulfurization was followed by ATR-IR, GC-MS. Aluminum salt ionic liquid analogue was found to have more than 90% removal of DBT from its mixture with decane (Model). The process in the Alum solvent was attributed to combination of an absorption and possibly oxidation of DBT through interaction of sulfur with the oxygen of sulfate group of the ionic liquid analogue when the IR bands of sulfate and hydrogen bond of ionic liquid analogue were influenced strongly by this interaction. The removal of dibenothiophene  was more effective at 30 ºC and 10 min than higher temperature and longer time.